Analysis That Influences Perceptions of Benefit, Convenience and Trust in Islamic Preferences For E-Wallet - Lisikmiko, Luthfi; Nurbaiti, Nurbaiti (Universitas Trunojoyo Madura, 2024)
This study aims to analyze the influence of perceived usefulness, perceived ease of use, and perceived trust on the decision to use e-wallets in Indonesia.This study uses a quantitative approach with a survey method, where data is collected by distributing questionnaires to e-wallet users. The sample of this study was selected using purposive sampling to ensure that respondents were active e-wallet users. This study involved 100 respondents from the Medan community. The data collected were then analyzed using multiple linear regression analysis with the help of SPSS software.The results of the study show that perceived usefulness, perceived ease of use, and perceived trust significantly influence the decision to use e-wallets. The perceived usefulness has been shown to have a positive impact, indicating that the higher the user's belief in the benefits provided by e-wallets, the greater the desire to use them. In addition, perceived ease of use shows that users tend to prefer e-wallets that are considered easy to use. Perceived trust also plays an important role in determining e-wallet usage, where users trust services that they consider safe and reliable. In conclusion, these three factors need to be considered by e-wallet service providers to increase user adoption, by strengthening the benefits, ease of use, and trust in their services.